Identification of Volatile Organic Compounds in Several Indoor Public Places in Korea - Sooyun Seo; Soogil Lim; Kiyoung Lee; Young-Kyo Seo; Sung-Ok Baek (Asian Journal of Atmospheric Environment, 2014)
A comprehensive profile of volatile organic compounds (VOCs) in public spaces is needed for interpreting indoor air measurements. Seasonal differences in profiles are critical for epidemiological study and risk assessment. The purposes of this study were to establish profiles for individual VOCs in 50 indoor public places in Korea and to determine seasonal variations in their concentrations. Air samples were taken during working hours. Seventy-two of the 91 targeted VOCs were identified using multiple standards. Six VOCs detected in all summer and winter samples were toluene, acetone, m,p-xylenes, ethylbenzene, benzene, and styrene. In summer, methyl ethyl ketone and 1-butanol were also found in all samples. In both seasons, the dominant indoor VOCs were toluene, m,p-xylenes, ethylbenzene, acetone, and isopropyl alcohol. Other chemicals associated with gasoline emissions were dominant in summer. Limonene was dominant only in winter due to the consumption of tangerines. The nine VOCs with the highest concentrations comprised 64.8% and 49.6% of the TVOC in summer and winter, respectively. Comparing two types of adsorbent tube, a single adsorbent tube with Tenax-TA had similar detection performance as a double adsorbent tube with Tenax and Carbotrap.